The Alleviating Effect of Perceived Supervisor Support on Workload, Work-Family Conflict & Learned Helplessness - Tayfur, Ã–.; Arslan, M. (Mediterranean Journal of Social Sciences, 2012)
The main purpose of this study is to examine the effects of perceived-workload and work-family conflict (WFC) on learnedhelplessness. While examining the role of the aforementioned variables, the effect of supervisor support was taken into account becausesupport given by supervisors is believed to alleviate the adverse impact of workload and WFC. A total of 155 people working in a privatebank in Turkey filled out the questionnaire. Participants rated the items that measure perceived workload, WFC, supervisor support andhelplessness. Moderated mediation analysis was conducted to reveal the direct and moderating effects. In general, the results werefound to be as expected. As employees experience high workload and WFC, their propensity to feel helplessness seems to increase.However, as perceived supervisor support increases, the adverse effect of WFC and workload on helplessness seems to diminish.However, it is noteworthy to say that the alleviating effect of support is effective up to some point. At high levels of workload and WFC,helplessness felt by employees increases substantially.